2022
DOI: 10.1002/lio2.750
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting operative autonomy and performance during otolaryngology training: A multicenter trial

Abstract: Objective Surgical education is changing in an era of new regulations and evolving training cultures. We sought to understand the factors that affect operative experiences during otolaryngology residency. Methods From December 2019 to December 2020, five otolaryngology training programs used the SIMPL OR smartphone application to evaluate residents after each operation. Residents and attendings rated the trainee's autonomy on a 4‐level Zwisch scale, performance on a 5‐level scale, and case complexity on a 3‐le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Prior studies have demonstrated an improvement in operative efficiency or error rate with formative feedback [ 13 , 27 29 ]. Peer-reviewed literature on resident performance shows a positive association between postgraduate year and operative performance and autonomy [ 30 ]. In practice, surgeons with higher case volumes and experience are noted to have shorter duration of surgery and improved performance and patient outcomes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated an improvement in operative efficiency or error rate with formative feedback [ 13 , 27 29 ]. Peer-reviewed literature on resident performance shows a positive association between postgraduate year and operative performance and autonomy [ 30 ]. In practice, surgeons with higher case volumes and experience are noted to have shorter duration of surgery and improved performance and patient outcomes [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Minimum case volume required for achievement of office procedure proficiency at the fellowship level will ultimately require case log data that does not currently exist, accounting for variability in both reporting and trainee ability to accurately self-assess performance. 16,17 Determination of minimum case volume for surgical mastery is an extensive and complex process when done correctly and was beyond the intended scope of the present study; however, we hope it will serve as a springboard for future research on this topic and eventually inform the development of national case benchmarks.…”
Section: Discussionmentioning
confidence: 99%